2014
DOI: 10.1007/s11682-014-9308-x
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in affective sharing and self–other distinction during empathic neural responses to others’ sadness

Abstract: Self-other distinction, the separation between self and other, is a prerequisite for empathy through which individuals share another individual's feelings. Prior research suggests that females are better at recognizing and sharing others' emotions, whereas males perform better at self-other distinction. It is unclear, however, whether this superiority in the self-other distinction occurs in males throughout the experience of empathy or only at some stages of the empathic process. The present study utilized eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(24 citation statements)
references
References 42 publications
4
20
0
Order By: Relevance
“…Previous studies suggest that, compared with neutral stimuli, negative stimuli would recruit more physiological and psychological resources due to the evaluation of evolutionary importance ( Yuan et al, 2007 ). Thus, negative stimuli elicit larger LPP amplitudes than neutral stimuli ( Luo et al, 2013 , 2015 ). Our results are consistent with these previous studies and indicate that empathic response could be found within three competitive intensity contexts at late cognitive controlled stage.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Previous studies suggest that, compared with neutral stimuli, negative stimuli would recruit more physiological and psychological resources due to the evaluation of evolutionary importance ( Yuan et al, 2007 ). Thus, negative stimuli elicit larger LPP amplitudes than neutral stimuli ( Luo et al, 2013 , 2015 ). Our results are consistent with these previous studies and indicate that empathic response could be found within three competitive intensity contexts at late cognitive controlled stage.…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies have indicated that empathy for pain include an early emotional sharing component (N2) and a late cognitive evaluation component (LPP) ( Luo et al, 2015 ; Cheadle, 2017). Moreover, grand averaged waveforms and topographical map of ERPs (see Figure 2 ) showed that those elicited by pain pictures and non-pain pictures in different competitive intensities were different and these differences were largest at frontal, central, and parietal sites.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We can speculate that the gender effects observed in solving the RMET are due to higher empathy levels in women than in men. Indeed, previous studies found that women were better at recognizing and sharing others’ emotions (Luo et al, 2014 ; Van der Graaff et al, 2014 ). Moreover, women showed also more often than men an empathizing style as reported by Billington et al ( 2007 ), therefore it becomes difficult to disentangle the role of sex and the role of a higher level of empathy.…”
Section: Discussionmentioning
confidence: 95%
“…It is assumed to be one of the main motivators for prosocial behaviour [21][22][23]. Since previous studies offer evidence for a correlation between gender and empathy [22,24,25], we performed an observational study to test the hypothesis that female nurses give higher amounts of PRN medication due to stronger affective empathy and emotional responsivity to other's pain and discomfort compared to men. The knowledge about gender-specific trends in the treatment of ICU patients may help to sensitize staff for personal medication patterns aimed at improving the quality of PRN medication therapy.…”
Section: Introductionmentioning
confidence: 99%